The cardiomyopathy of cystic fibrosis: a modern form of Keshan disease - Segovia-Cubero, Javier; Ruiz-Bautista, Lorena; Maiz-Carro, Luis; Girón-Moreno, Rosa M.; Prados-Sánchez, M. Concepción; Martínez-Martínez, M. Teresa; González-Estecha, Montserrat; Mingo-Santos, Susana; Gómez-Bueno, Manuel; Salas-Antón, Clara; Cavero-Gibanel, Miguel A.; Pastrana-Ledesma, Miguel; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction We conducted a study to determine the prevalence of structural heart disease in patients with CF, the characteristics of a cardiomyopathy not previously described in this population, and its possible relationship with nutritional deficiencies in CF. Methods We studied 3 CMP CF patients referred for heart-lung transplantation and a prospective series of 120 adult CF patients. All patients underwent a clinical examination, blood tests including levels of vitamins and trace elements, and echocardiography with evaluation of myocardial strain. Cardiac magnetic resonance imaging (CMR) was performed in patients with CMP and in a control group. Histopathological study was performed on hearts obtained in transplant or necropsy. Results We found a prevalence of 10% (CI 4.6%–15.4%) of left ventricular (LV) dysfunction in the prospective cohort. Myocardial strain parameters were already altered in CF patients with otherwise normal hearts. Histopathological examination of 4 hearts from CF CMP patients showed a unique histological pattern of multifocal myocardial fibrosis similar to Keshan disease. Four of the five CF CMP patients undergoing CMR showed late gadolinium uptake, with a characteristic patchy pattern in 3 cases (p < 0.001 vs. CF controls). Selenium deficiency (Se < 60 µg/L) was associated with more severe LV dysfunction, higher prevalence of CF CMP, higher NTproBNP levels, and more severe pulmonary and digestive involvement. Conclusion 10% of adults with CF showed significant cardiac involvement, with histological and imaging features resembling Keshan disease. Selenium deficiency was associated with the presence and severity of LV dysfunction in these patients.